Pengaruh Kualitas Pelayanan, Suasana Toko Dan Keragaman Produk Terhadap Niat Beli Ulang Melalui Kepuasan Sebagai Variabel Intervening (Study Pada Sardo Swalayan Kota Malang) - La Jaber; Muhammad Ridwan Basalamah; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2021)
Abstract This research was conducted by researchers with the intent and purpose of being able to determine the effect directly or indirectly between service quality, shop atmosphere and product diversity on repurchase intention and where the three dependent variables affect repurchase intention through customer satisfaction. first to Sardo supermarkets in Malang City. This research is a type of explanatory research using a quantitative approach. The population obtained in the study was 500 respondents with a sample of 80 respondents, the sample was obtained using the Slovin formula and with the criteria that have been determined by the researcher. In this research data collection using a questionnaire instrument.This study resulted in the conclusion that all independent variables, namely service quality, shop atmosphere and product diversity can affect satisfaction and repurchase intention at Sardo supermarkets in Malang City, where the resulting influence can be said to be significant and have a positive effect, and satisfaction can mediate the effect of the three independent variables on repurchase intention. Keywords: Service Quality, Shop Atmosphere, Product Diversity, Satisfaction and Repurchase Intention.